2022
DOI: 10.33073/pjm-2022-040
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genome Analysis of a Novel Alkaliphilic Actinobacterial Species Nesterenkonia haasae

Abstract: In the present study, a comparative genome analysis of the novel alkaliphilic actinobacterial Nesterenkonia haasae with other members of the genus Nesterenkonia was performed. The genome size of Nesterenkonia members ranged from 2,188,008 to 3,676,111 bp. N. haasae and Nesterenkonia members of the present study encode the essential glycolysis and pentose phosphate pathway genes. In addition, some Nesterenkonia members encode the crucial genes for Entner-Doudoroff pathways. Some Nesterenkonia members possess th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…The strain LY-0111 T was maintained on TSA medium and stored as aqueous glycerol suspensions (20%, v/v) at -80°C. N. ava CCTCC AB 207010 T (Luo et al 2008) and N. haasae Hz 6-5 T (Wang et al 2022;Wang et al 2021) were used as reference strains for morphological, physiological, biochemical and chemotaxonomic analyses under the same experimental conditions as strain LY-0111 T .…”
Section: Bacteria Isolate and Culture Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The strain LY-0111 T was maintained on TSA medium and stored as aqueous glycerol suspensions (20%, v/v) at -80°C. N. ava CCTCC AB 207010 T (Luo et al 2008) and N. haasae Hz 6-5 T (Wang et al 2022;Wang et al 2021) were used as reference strains for morphological, physiological, biochemical and chemotaxonomic analyses under the same experimental conditions as strain LY-0111 T .…”
Section: Bacteria Isolate and Culture Conditionsmentioning
confidence: 99%
“…Comparative genome analyses of Nesterenkonia strains highlights their potential as sources of biologically active molecules and as models for understanding microbial adaptation strategies in natural environments. They possess a large number of carbohydrate-related genes (such as halophilic αamylases and thermostable xylanases), as well as genes involved in butanol fermentation and saccharide utilization (Aliyu et al 2016; Wang et al 2022). They were also reported to be multi-resistant, especially to cold stress, UV radiation, drought, and copper, and be able to dissolve CaCO 3 and MgCO 3 (Orhan et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Genome sequencing coupled with advancements in bioinformatic tools provides valuable insights into bacterial evolution, ecology, taxonomy, pathogenesis, metabolism, and the design of related therapeutic interventions ( Goris et al, 2007 ; Donkor, 2013 ; Wang et al, 2022 ). Our earlier microbial analysis of Chilean hot springs showed that they harbor bacteria with thermostable EPSs and bioactive molecules ( Banerjee et al, 2022 ; Marín-Sanhueza et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%